Pengaruh Content Marketing, Online Customer Review dan Word of Mouth terhadap Keputusan Pembelian melalui Kepercayaan Konsumen sebagai Variabel Intervening pada Pengguna Marketplace sebagai Tiktok Produk Fashion - Detra Ayu Puspitasari; Noventia Karina Putri; Prianka Ratri Nastiti (Yayasan Al Ma'arif Dawuhan, 2025)
This study aims to examine and analyze the influence of content marketing, online customer reviews, and word of mouth on purchasing decisions through consumer trust as an intervening variable among marketplace users of TikTok fashion products. This research adopts a quantitative approach. The population consists of FEB Management students at Universitas PGRI Semarang, class of 2021, with a sample size of 302 students. Data collection was conducted by distributing online questionnaires via Google Forms. The data analysis techniques used in this study include structural model analysis (Inner Model), measurement model analysis (Outer Model), and hypothesis testing. Data processing was carried out using SmartPLS 4.0.9.9 software. The findings of this study indicate that content marketing, word of mouth, and purchasing decisions significantly influence consumer trust. However, online customer reviews do not significantly affect consumer trust. Furthermore, content marketing and word of mouth significantly influence purchasing decisions, whereas online customer reviews do not. Additionally, word of mouth can influence purchasing decisions through consumer trust as an intervening variable. However, content marketing and online customer reviews do not affect purchasing decisions through consumer trust as an intervening variable.